Performance of Body Weight and Body Dimension Measurements of Tolaki Chickens Ages 1 to 8 Weeks - Saili, Takdir; Nafiu, La Ode; Pagala, Muhammad Amrullah; Albar, Fahry; Zulkarnain, Deki; Munadi, La Ode Muh. (Pascasarjana Universitas Halu Oleo, 2024)
Tolaki chicken is a native breed originating from Southeast Sulawesi, and it is distributed across various regions, including Konawe, South Konawe, Kolaka, East Kolaka, and North Konawe Regencies. These chickens are predominantly utilized for cockfighting purposes. The objective of this study is to analyze the body weight and body dimensions performance of Tolaki chickens aged 1 to 8 weeks. Descriptive analysis was employed for the research data, presenting mean (X̅), standard deviation (SD), and coefficient of variance. The observed variables in this study, along with the measurement methods, included (1) body weight (kg), measured using a scale with a capacity of 2 kg and an accuracy level of 0.01, (2) back length (cm), measured by determining the distance between the last cervical vertebrae and the caudal vertebral bones, (3) chest circumference (cm), measured at the base of the right wing straight down to the sternum bone to the base of the right wing using a measuring tape, (4) wing span length (cm), measured from the humerus bone to the phalanges on both wings using a measuring tape, and (5) shank length (cm), measured from the tibia joint to the beginning of the middle finger joint, using a measuring tape. The study results indicate that body weight increased with age, and the body dimensions of chest circumference and back length experienced a significant increase at 12 weeks of age.